Non-biological factors associated with postpartum depression among women in Shenzhen: a case-control study - He, Jiangshan; Li, Yang; Chen, Ling; Zhang, Ying (Frontiers in Public Health, 2024)
Background. Postpartum depression (PPD) presents a significant public health challenge. While PPD's impact extends from maternal health to child development, cultural stigma and a lack of public awareness, particularly in developing countries, contribute to its underestimation and under diagnosed. This study investigated the nonbiological associated factors for PPD in Shenzhen city due to its unique socioeconomic landscape, where rapid urbanization and migrant influx could uniquely impact maternal mental health. By identifying local PPD determinants, the research aimed to contribute to targeted mental health interventions in the region.Method. Data were collected from May to December 2019 at the Luohu Maternal and Child Health Medical Centre, Shenzhen. Inclusion criteria were postpartum women without psychiatric histories who live within the locality. The Chinese Edinburgh Postnatal Depression Scale was utilized to confirm PPD diagnosis. Participant information including demographics, economic status and postnatal factors were collected via structured questionnaires. Statistical analyses of t-tests, Wilcoxon ranksum tests, chi-square tests, and logistic regression, were performed using SPSS 20.0, with significance set at p ≤ 0.05.The study included 430 healthy mothers and 73 PPD mothers. Several factors were found to significantly influence the onset of PPD (p < 0.05): age (OR = 0.921, 95%